2021
DOI: 10.1108/bjm-12-2020-0449
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity and firms' internationalization speed: the role of female directors' characteristics

Abstract: PurposeDrawing on the gender self-schema theory, upper echelons theory and the literature on international business, this study aims to examine the impact of board gender diversity on firms' internationalization speed.Design/methodology/approachIn this study, secondary data of 886 listed Chinese manufacturing firms from 2009 to 2018 are studied using the ordinary least squares regression model as the baseline method, an instrumental variable method is adopted for endogeneity control and both fixed and random e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…With regard to board composition, two main questions are of crucial importance for management research (Dobija et al, 2022;Ren and Zeng, 2022;Porcena et al, 2021;Krause et al, 2019;Li and Huang, 2019;Aluchna and Kaminski, 2017). The first question concerns the impact of board diversity on company performance.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to board composition, two main questions are of crucial importance for management research (Dobija et al, 2022;Ren and Zeng, 2022;Porcena et al, 2021;Krause et al, 2019;Li and Huang, 2019;Aluchna and Kaminski, 2017). The first question concerns the impact of board diversity on company performance.…”
Section: Discussionmentioning
confidence: 99%
“…HR managers who participated in the KWMP study reported the numbers of female and male board directors. Previous studies measured gender diversity in board director positions as the proportion of women to the total number of board directors (Ren and Zeng, 2022). Therefore, for each company, we divided the number of female board directors by the total number of board directors to operationalize the gender diversity of the boards in accordance with the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Sherman et al (1998) find that a higher proportion of outsider directors, which should increase heterogeneity, may dampen internationalisation. A more recent study finds that board-level gender diversity can reduce the speed of internationalising as women are less prone to overconfidence bias and tend to be more cautious, conservative decision-makers (Ren and Zeng, 2021). This range of findings regarding board heterogeneity and internationalisation speed provides further evidence that how boards shape the internationalisation process of INVs needs more scholarly attention.…”
Section: Conceptual Background and Expected Theoretical Patternsmentioning
confidence: 99%
“…Overall, it is well established that INVs’ human and social capital are often critical to ensuring the timely revision of their knowledge base to maintain their internationalisation speed and competitiveness. However, the contribution of boards to the knowledge acquisition process and their more direct shaping influence on the management of INVs is under-researched (Prashantham and Floyd, 2019; Ren and Zeng, 2021).…”
Section: Introductionmentioning
confidence: 99%